The Main Stages of the Russian Expansion on Azerbaijan at the XVIII and Beginning of the XIX Centuries - Gozalova, Nigar (Richtmann Publishing, 2012)
During practically its entire history Azerbaijan was objective involved in processes geopolitical and, foremost military andpolitical expansion. In this article we consider the main stages of the military expansion of Russian empire in northern Azerbaijan duringof the XVIII and beginning of the XIX centuries. It was in the XVIII century military-political situation on South Caucasus characterized bystrengthening of activity in the region of three regional powers - Russia (only starts to gain positions in the region), as well as Iran andthe Ottoman Empires (more and more losing its positions). Thus, the main focus of Russia's imperial policy in the Caucasus at the XVIIIand beginning of the XIX centuries was to create a Â«bufferÂ» zone, with a view to establishing a military base for opposition to thedominant in the region neighboring states: Ottoman Empire and Qajar Iran. As a result, the main victim of policies carried out by Russiain the Caucasus was, of course, the people of Azerbaijan, which lost part of their historic lands.